2015
DOI: 10.1095/biolreprod.115.130252
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Fertility and Altered Epididymal and Sperm Integrity in Mice Lacking ADAM71

Abstract: The mammalian epididymis is a highly convoluted tubule that connects the testis to the vas deferens. Its proper functions in sperm transport, storage, and maturation are essential for male reproduction. One of the genes predominantly expressed in the epididymis is ADAM7 (a disintegrin and metalloprotease 7). Previous studies have shown that ADAM7 synthesized in the epididymis is secreted into the epididymal lumen and is then transferred to sperm membranes, where it forms a chaperone complex that is potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…Despite their common characteristics for processing and localization, except for ADAM1, these ADAM proteins differ in the regulation and maintenance of their integrity. Previous studies based on the protein expression phenotypes in mouse KO models of Adam1a , Adam1b , Adam2 , Adam3 , Adam6 , and Adam7 have indicated that these ADAMs have intricate regulatory relationships (Figure ; Cho et al, , ; Kim, Yamashita, et al, 2006; Nishimura et al, ; Shamsadin et al, ; Voronina et al, ; Yamaguchi et al, ). In Adam1a ‐null mice, ADAM1B and ADAM2 are expressed normally in both testicular germ cells and epididymal mature sperm.…”
Section: Testis‐specific Adam Proteins (Adam1a 2 3 6)mentioning
confidence: 99%
See 4 more Smart Citations
“…Despite their common characteristics for processing and localization, except for ADAM1, these ADAM proteins differ in the regulation and maintenance of their integrity. Previous studies based on the protein expression phenotypes in mouse KO models of Adam1a , Adam1b , Adam2 , Adam3 , Adam6 , and Adam7 have indicated that these ADAMs have intricate regulatory relationships (Figure ; Cho et al, , ; Kim, Yamashita, et al, 2006; Nishimura et al, ; Shamsadin et al, ; Voronina et al, ; Yamaguchi et al, ). In Adam1a ‐null mice, ADAM1B and ADAM2 are expressed normally in both testicular germ cells and epididymal mature sperm.…”
Section: Testis‐specific Adam Proteins (Adam1a 2 3 6)mentioning
confidence: 99%
“…With the exception of Adam1b ‐null mice, these KO mice exhibit complicated phenotypes of fertilization defects, among which Adam1a , Adam2 , Adam3 , and Adam6 ‐deficient male mice are sterile because of a failure of the sperm to pass through the UTJ in the female genital tract (Cho et al, ; Kim, Yamashita, et al, 2006; Nishimura, Kim, Nakanishi, & Baba, ; Shamsadin et al, ; Voronina et al, ; Yamaguchi et al, ). The phenotypes of Adam7 ‐null mice slightly differ from those of Adam1a −/− , Adam2 −/− , Adam3 −/− , and Adam6 −/− strains (Choi et al, ). The sperm from Adam7 ‐deficient mice display decreased motility and tail deformation (Choi et al, ).…”
Section: Testis‐specific Adam Proteins (Adam1a 2 3 6)mentioning
confidence: 99%
See 3 more Smart Citations